(untitled) (Conferencea, 2024)
This article, based on a comparative approach, scientifically analyzes the spiritual and ethical segment of increasing the efficiency of civil servants. The article also scientifically substantiates that the development of moral qualities of civil servants is a very important task of the state at all times and in all places.